Socioeconomic impacts with the implementation of the railroad EF-118 RJ/ES: comparison of cargo logistics at the Port of Açu (Research, Society and Development, 2020)
Since the beginning of operations in 2014, Port of Açu has shown significant growth in relation to cargo handling, with all demand dependent on road transport. However, there is a proposal for the implementation of the EF-118 railway that would interconnect Rio de Janeiro and Vitória, serving the region of Port. This work seeks to economically evaluate the advantages of the implementation of the railway modal compared to the roadway already used in the region. Due to the intense flow of cargo in the Industrial-Port Complex, the possibility of building a new highway, the RJ-244, is being studied, extending from the industrial district to BR-101. For this purpose, surveys were conducted to determine the average daily volume of vehicles circulating in the region, in addition to the different types of cargo transported and their relationship with Port. Based on the information collected in the Traffic Studies Report issued, it was possible to relate data and achieve at the value of the average annual daily volume for each category of cargo handled in the Port. Bearing in mind that in 2019, Port of Açu handled approximately 751 thousand tons of cargo and analyzing the estimated costs by ABIFER for road and rail transport, the approximate cost values for each one per ton of cargo per kilometer were reached. Comparing values, it is possible to notice that the cost of transporting cargo by rail corresponds to about 16.6% of the amount spent on transporting of the same weight of cargo by road, which means a considerable advantage for its implementation.